2022
DOI: 10.54055/ejtr.v31i.2212
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering with elephants: Is it a way of moving towards global citizenship?

Abstract: This study examines the nature of European volunteer tourists’ experiences at Elephants World, Thailand as well as whether and/or to what extent such experiences foster a sense of global citizenship among them. It used an interpretive paradigm and a qualitative research approach. The informants included 21 volunteer participants from European countries. A combination of semi-structured interviews and participant observation was used to gather data. Data were then analysed via a thematic analysis technique, rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Global identity has been linked to the promotion of PEB and the mitigation of environmental problems and climate change. Studies were found not just in psychology ( Reysen, 2022 ) but also in business ( Russell and Russell, 2010 ), political science ( Chung and Milkoreit, 2021 ), education ( Wynveen et al, 2012 ), and tourism ( Proyrungroj, 2022 ). Given the growing interests in global identity and PEB and EC, an in-depth systematic review of our understanding of this relationship thus far is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Global identity has been linked to the promotion of PEB and the mitigation of environmental problems and climate change. Studies were found not just in psychology ( Reysen, 2022 ) but also in business ( Russell and Russell, 2010 ), political science ( Chung and Milkoreit, 2021 ), education ( Wynveen et al, 2012 ), and tourism ( Proyrungroj, 2022 ). Given the growing interests in global identity and PEB and EC, an in-depth systematic review of our understanding of this relationship thus far is warranted.…”
Section: Introductionmentioning
confidence: 99%